THE INFLUENCE OF JOT THOUGHTS TOWARDS STUDENTS’ WRITING ABILITY IN DESCRIPTIVE TEXT - Nurchurifiani, Eva (Lentera: Jurnal Ilmiah Kependidikan, 2017)
The problem of this research is many students get difficulties in writing especially in writing descriptive text. In this research the researcher tried to investigate Jot Thoughts in teaching writing. The objective of this research are to know and describe the significant of the influence of Jot Thoughts towards students’ writing ability in Descriptive text, and to know and describe the average score of students’ writing ability in writing Descriptive text which is taught through Jot Thoughts higher than which is taught through conventional technique. The research was conducted at eight grade students of SMPN 3 Pardasuka, Pringsewu in 2016/2017. In this research the researcher used experimental method. The population of the this research are 80 students in 3 classes. The sample of the research were two classes, the first class was VIII A consisted of 26 students as the experimental class and the second class was VIII C consisted of 26 as the control class. In the experimental class was the students were taught by Jot Thoughts and in control class the students were taught by using the conventional technique. In conducting the research, the writer used Cluster Random Sampling technique to establish the experiment class and the control class, because all students were the sample is homogeneous. In data collecting technique, it was used written test, it is include instruction that students should make a composition which consist at least 100 words based on the topic chosen. In data analysis, the writer used t-test formula. It was found that ttest > ttable = 2.85 > 2.02. It means that Hα is accepted. So, the researcher concluded that there is the influence of using Jot Thoughts towards students’ writing ability in Descriptive text at eighth class of SMP Negeri 3 Pardasuka Pringsewu in 2016/2017.